Dietary medium chain triglycerides impairs orexigenic action of ghrelin in mice - Aotani, Daisuke; Ariyasu, Hiroyuki; Tanaka, Tomohiro; Shimazu-Kuwahara, Satoko; Nomura, Hidenari; Shimizu, Yoshiyuki; Takeda, Katsushi; Koyama, Hiroyuki; Kusakabe, Toru; Miyazawa, Takashi; Hikida, Takatoshi; Kataoka, Hiromi; et al. (Frontiers in Endocrinology, 2026)
IntroductionGhrelin, a stomach-derived hormone, increases food intake and body weight. Efforts have been made therefore to modulate ghrelin signaling for the treatment of obesity or emaciation. However, basic biology of the potential effects of dietary nutrients on ghrelin action has not yet been fully uncovered.MethodsTo investigate an impact of fat intake on orexigenic effect of ghrelin, we examined ghrelin transgenic mice or mice treated with ghrelin fed with the diet containing medium-chain triglycerides (MCT).ResultsFive-day MCT diet feeding increased plasma ghrelin levels by 2.5-fold compared with long-chain triglyceride (LCT)-fed mice, potentially through O-acyltransferase-mediated medium-chain fatty acylation and maturation of ghrelin. The plasma ghrelin levels of ghrelin and O-acyltransferase double transgenic mice (ghrelin-Tg) reached ten times higher than wild-type (WT) littermates under the MCT diet. The rise of plasma ghrelin levels in ghrelin-Tg, however, was not associated with any changes in food intake or body weight. Administration of ghrelin significantly increased food intake in WT mice under the normal chow (NC) or the LCT diet. In contrast, ghrelin-induced increase of food intake was not observed under the MCT diet. Consistently, upregulation of hypothalamic expression of neuropeptide Y (NPY), a critical mediator of orexigenic action by ghrelin, was observed under the NC or the LCT diet, but not under the MCT diet. Meanwhile, enhancement of food intake by the intracerebroventricular injection of NPY was preserved in mice fed with the MCT diet, suggesting an interference of ghrelin signaling upstream of NPY. Interestingly, ghrelin-induced growth hormone (GH) secretion was not attenuated by the MCT diet, indicating a distinct pathway for appetite and GH regulation.DiscussionOur results provide evidence for the MCT-induced attenuation of the orexigenic effect of ghrelin, and suggest a novel interplay between dietary lipids and hormone signaling.